2009
DOI: 10.1088/1468-6996/10/1/014605
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of magnetic field processing on the texture, phase assemblage and properties of low aspect ratio Bi2Sr2CaCu2Ox/AgMg wire

Abstract: Bi 2 Sr 2 CaCu 2 O x /AgMg conductors are potentially important for many applications up to 20 K, including magnets for cryogen-free magnetic resonance imaging and high field nuclear magnetic resonance research. One promising approach to increased critical current density is partial-melt processing in the presence of a magnetic field which has been shown to enhance c-axis texturing of wide, thin tape conductors. Here, we report on low aspect ratio rectangular conductors processed in an 8 T magnetic field. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Another important feature in Bi2212 RW microstructures is interfilamentary bridges connecting neighboring Bi2212 filaments. Studies of non-densified wires have shown that two types of bridges exist within Bi2212 RWs, smaller bridges (<2 μm) that are the result of outgrowths from one filament reaching another and which do not enhance transport, and larger bridges (2-4 μm in width) which play a key role in facilitating long-range transport in Bi2212 RWs by providing superconducting pathways for electron transport that bypasses defects [6,9,10]. In high J c densified wires, in which there is less porosity to bypass within the filaments, the role of interfilamentary bridges may be less significant.…”
Section: Role Of Defects In Bi2212 Rwsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important feature in Bi2212 RW microstructures is interfilamentary bridges connecting neighboring Bi2212 filaments. Studies of non-densified wires have shown that two types of bridges exist within Bi2212 RWs, smaller bridges (<2 μm) that are the result of outgrowths from one filament reaching another and which do not enhance transport, and larger bridges (2-4 μm in width) which play a key role in facilitating long-range transport in Bi2212 RWs by providing superconducting pathways for electron transport that bypasses defects [6,9,10]. In high J c densified wires, in which there is less porosity to bypass within the filaments, the role of interfilamentary bridges may be less significant.…”
Section: Role Of Defects In Bi2212 Rwsmentioning
confidence: 99%
“…The resolidification from the peritectic melt results in a heterogeneous microstructure; in addition to the desired Bi2212 phase, porosity and a variety of other phases, including Bi 2 Sr 2 CuO z (Bi2201), alkaline earth cuprates (AEC) and copper-free phases [8], are present in fullyprocessed wires. Furthermore, during resolidification, Bi2212 grains penetrate the Ag matrix, resulting in 'outgrowths' and interfilamentary bridges [9,10]. Figure 1(b) shows a crosssectional scanning electron microscopy (SEM) image of a fully-processed wire, illustrating the heterogeneous microstructure.…”
mentioning
confidence: 99%
“…Magnetic texturing of Ag-sheathed tapes was studied in very high fields and lead to high critical current densities [27,[29][30][31][32]. E. Flahaut demonstrated in his PhD the possibility to texture highly homogeneous Bi2212 tapes by moving the tape in the furnace and using a continuous melting process with large critical currents (Jc = 230kA/cm 2 at 4.2K, self field) [33].…”
Section: Ag-sheated Tapes Of Bi2sr2cacu2o8+xmentioning
confidence: 99%
“…Additionally, all these conductors offer a wide variety of aspect ratios. When MgB 2based and Bi-based tapes have α up to few tens [29,35,36], YBCO conductors typically have α of several thousands, but on introducing striations, α can decrease to around 100 [37].…”
Section: Introductionmentioning
confidence: 99%